Long Live Technical Translation: Technical Translation in English Language Learning - E. A. Komochkina; T. V. Selezneva (Высшее образование в России)
The article highlights the urgent need for a new approach to teaching ESP (English for professional purposes) to Master’s applicants specializing in Physics and Mathematics. Therefore, a comparative analysis of textbooks and methods has been carried out to draw a parallel between traditional and innovative approaches to teaching foreign languages in technical tertiary institutions. The analysis has revealed the insufficiency of comprehensive ESP methodologies particularly in terms of teaching would-be mathematicians and physicists considering the science-students’ mindset. The latter should be primarily taken into account to ensure that the selection and submission of educational materials are tailored to the needs of science modes of thinking, namely, coherent and cohesive presentation of a project and its results and arguments; unified forms of presented achievements; academic command of style; concise and laconic content; universal “schemes” of presenting results. Within this context the role of extracurricular autonomous studies has been reconsidered and re-evaluated as far as language learning skills and competences are concerned. Particularly, benefits and drawbacks of individual work with an academic article have been examined as well as the current online availability of material and the extent of teacher’s involvement. The article stresses the need of transforming the conventional teaching models of technical translation and science-literature reading into a new form of seminar-workshop consultation. Its distinctive features and key principles would include its correlation with physical and mathematical disciplines, the use of specific formulaic expressions. The conclusion advances an idea based on some theoretical evidence of close integration between English and science departments to provide a Master’s applicant with relevant skills and competencies for professional communication in English.